2018
DOI: 10.1007/s10461-018-2210-6
|View full text |Cite
|
Sign up to set email alerts
|

Level of Alcohol Use Associated with HIV Care Continuum Targets in a National U.S. Sample of Persons Living with HIV Receiving Healthcare

Abstract: We evaluated associations between levels of alcohol use and HIV care continuum components using national Veterans Aging Cohort Study data for all patients with HIV and AUDIT-C screening (2/1/2008-9/30/2014). Poisson regression models evaluated associations between alcohol use levels (non-drinking, low-, medium-, high-, and very high-level drinking) and: (1) engagement with care (documented CD4 cells/µl or viral load copies/ml labs), (2) ART treatment (≥ 1 prescription), and (3) viral suppression (HIV RNA < 500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 61 publications
1
57
2
2
Order By: Relevance
“…AUD is a significant comorbidity in PLWH contributing to poor health outcomes (Vagenas et al, 2015; Edelman et al, 2018). Alcohol use disorder interferes with HIV disease management on multiple levels which impact the HIV care continuum (Claborn et al, 2018; Vagenas et al, 2015; Williams et al, 2019). However, the evidence of physiological consequences of alcohol use among PLWH is limited due to the tools used to assess and measure alcohol use frequency, quantity, duration, and patterns.…”
mentioning
confidence: 99%
“…AUD is a significant comorbidity in PLWH contributing to poor health outcomes (Vagenas et al, 2015; Edelman et al, 2018). Alcohol use disorder interferes with HIV disease management on multiple levels which impact the HIV care continuum (Claborn et al, 2018; Vagenas et al, 2015; Williams et al, 2019). However, the evidence of physiological consequences of alcohol use among PLWH is limited due to the tools used to assess and measure alcohol use frequency, quantity, duration, and patterns.…”
mentioning
confidence: 99%
“…2 Center for Interdisciplinary Research on AIDS, Yale School of Public Health, New Haven, CT 06510, USA. 3 Syracuse University, Syracuse, NY 13244, USA. 4 College of Public Health, University of Georgia, Athens, GA 30602, USA.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…may interfere with achievement of HIV viral suppression [3], increase risk of morbidity and mortality [4][5][6], and lead to risk behaviors and ongoing HIV transmission [7]. Accordingly, guidelines recommend that patients with atrisk alcohol use, including those with HIV, should receive brief interventions with subsequent treatment to reduce their alcohol use [8,9] and integrated with HIV care [10].…”
mentioning
confidence: 99%
“…Besides, it has been reported that alcohol use is associated with an increase in the risk of chronic illnesses such as cardiovascular disease and cancer in people living with HIV [18][19][20][21][22]. Alcohol use among people living with HIV affects negatively on their adherence and engagement to the HIV treatment, treatment outcomes and mortality risk [7,[23][24][25]. There are various pharmacological/behavioral treatments for treating AUDs [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%